If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + 3x) + -1 = 47 (3 * 4 + 3x * 4) + -1 = 47 (12 + 12x) + -1 = 47 Reorder the terms: 12 + -1 + 12x = 47 Combine like terms: 12 + -1 = 11 11 + 12x = 47 Solving 11 + 12x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 12x = 47 + -11 Combine like terms: 11 + -11 = 0 0 + 12x = 47 + -11 12x = 47 + -11 Combine like terms: 47 + -11 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 5-2y=11-8y+6y | | .66m-.6m=4 | | 3x-6+6x=-15 | | 6(-2x-2)=-72 | | 1+3n-5n-4=1-4n | | 93-(7x+12)=7(x+3)+x | | .5xh+.33x(h-6)=.83xh+2 | | -5(t-5)+8t=6t-1 | | 5x-5=-3x-9 | | (x/3-6)=(2x+4)(-1/2) | | 3(y-5)-5y=5y+9 | | 8-4z=16 | | 7x-8=7x-8 | | 8x-3y=6-4x | | 13=.167x+2y | | -3(t-4)+7t=8t-6 | | 4x+3y+2x+y= | | -7(t-2)-(t+1)=4 | | 5y^2-2y+4=0 | | (x+4)(x+4)+4=53 | | 4k+2-3k=18 | | 16+5w-10-(-3w)=10-12 | | 6x-8=6(x-4) | | x^2-17x+21=0 | | 7=(n/7)+9 | | 7k+5=-19 | | -4-3n=-13-6n | | 4k+2-3k=16 | | (2t-3)(2t+1)=5 | | 17-3d+8-4d=-9+13 | | 5-5d-6-5d= | | (x^2)-10x+16=0 |